Knowing no limits: First record of Ozognathus cornutus (Coleoptera: Ptinidae: Anobiinae) in Greece, including new host-plant records - Koutsoukos, Evangelos; Demetriou, Jakovos (ENTOMOLOGIA HELLENICA, 2023)
Ozognathus cornutus (LeConte, 1859), a species native to the Nearctic zoogeographical realm, has gradually spread throughout Europe and the Mediterranean region becoming alien. The species has been associated with at least 41 host-plant species and has been detected in both man-made and natural habitats. Nevertheless, no phytosanitary measures have been applied or adverse impacts on native biodiversity recorded. In this publication, O. cornutus is recorded in Greece from Rhodes Island, constituting the first record of this alien species to the country. In addition, examination of material from Cyprus and Greece unveils four new host-plants for the species, Asphodelus ramosus, Schinus terebinthifolia, Schinus molle and Vachellia farnessiana.